Computer-aided diagnosis of breast cancer using bi-dimensional empirical mode decomposition - Bajaj, Varun; Pawar, Mayank; Meena, Vinod Kumar; Kumar, Mukesh; Sengur, Abdulkadir; Guo, Yanhui (Springer London Ltd, 2019)
Breast cancer is a serious disease for women in the world and ranks the second cancer for women in many countries. Computer-aided diagnosis provides a second view to aid for radiologists to detect and diagnose breast cancer. In this paper, we present a novel approach of textural features extraction from mammograms using bi-dimensional empirical mode decomposition (BEMD) method and classification for diagnosis of breast cancer. Preprocessing techniques such as noise removal, artifacts and background suppression and contrast enhancement are performed before features extraction stage. Gray-level co-occurrence matrices-based features are extracted from 2-D intrinsic mode functions obtained by applying BEMD method on mammographic images. Finally, these features are given as an input to least squares support vector machine for classification of mammogram as normal or abnormal. The experimental results show that the proposed method achieves 95% accuracy, which is better than as compared to other published methods in the Mini-MIAS database for diagnosis of breast cancer. The proposed method can be used as automatic, accurate and noninvasive method for breast cancer diagnosis and treatment.
Keywords: Bi-dimensional empirical mode decomposition (BEMD); Breast cancer; Gray-level co-occurrence matrices (GLCM)